2019
DOI: 10.1175/waf-d-19-0028.1
|View full text |Cite
|
Sign up to set email alerts
|

Track Uncertainty in High-Resolution HWRF Ensemble Forecasts of Hurricane Joaquin

Abstract: Hurricane Joaquin (2015) was characterized by high track forecast uncertainty when it approached the Bahamas from 29 September 2015 to 1 October 2015, with 5-day track predictions ranging from landfall in the United States to east of Bermuda. The source of large track spread in Joaquin forecasts is investigated using an ensemble prediction system (EPS) based on the Hurricane Weather Research and Forecasting (HWRF) Model. For the first time, a high-resolution analysis of an HWRF-based EPS is performed to isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 58 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…To address the TC-centric limitation of the operational HWRF, an experimental version of HWRF, known as the Basin-scale HWRF (HWRF-B; Table 1; X. Alaka et al 2017Alaka et al , 2019Alaka et al , 2020 12 within a large, static parent domain that includes most of the areas of responsibility of NHC and NOAA's Central Pacific Hurricane Center (CPHC) (Fig. 2).…”
Section: The Basin-scale Hwrf Modeling System and Experimental Designmentioning
confidence: 99%
“…To address the TC-centric limitation of the operational HWRF, an experimental version of HWRF, known as the Basin-scale HWRF (HWRF-B; Table 1; X. Alaka et al 2017Alaka et al , 2019Alaka et al , 2020 12 within a large, static parent domain that includes most of the areas of responsibility of NHC and NOAA's Central Pacific Hurricane Center (CPHC) (Fig. 2).…”
Section: The Basin-scale Hwrf Modeling System and Experimental Designmentioning
confidence: 99%
“…Here, and for this hindcasted case, the deterministic run and mean of ensembles are quite close to each other. However, it has been proven that a welldesigned ensemble system will not only help represent the uncertainty (and spread) well but it will also give us better products (Alaka et al 2019;Zhang et al 2014) compared to deterministic simulation, especially in forecast. Although the uncertainty is small at the beginning, the errors can grow fast due to the aforementioned key roles; therefore, the simulated results will diverge from observation.…”
Section: Atmospheric Modelmentioning
confidence: 99%
“…Some research [12,36] indicated that the forecast uncertainty of a TC track has a great influence on its intensity. After a TC makes landfall, it will often stop intensifying and even decay rapidly.…”
Section: Tc Track Sensitivitymentioning
confidence: 99%